Heroes of the american west - Sanford, William R. (William Reynolds), 1927-; Green, Carl R. (Berkeley Heights, NJ : Enslow Publishers, Inc., 2013)
"Explores the life of Bill Pickett, the African-American cowboy who invented bulldogging, from his childhood in Texas to his life as a working cowboy to his career as a rodeo star"--Provided by publisher.
Includes bibliographical references (p. 47) and index.
Keywords: African American cowboys -- Biography